2012
DOI: 10.1097/mnh.0b013e3283522ea8
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of membranous nephropathy

Abstract: The identification of target antigens provides new tools for diagnosis, prognosis and monitoring of therapy in human membranous nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 39 publications
0
20
1
3
Order By: Relevance
“…Membranous nephropathy (MN) is another form of immune-mediated glomerular injury in which immune complexes of immunoglobulins and complement accumulate in a granular pattern along the outer side of the GBM, leading to glomerular visceral epithelial cell detachment 90 (see the articles by Beck et al and Takano and Cybulsky). Seminal studies have identified several autologous antigens that are targets of antibody response in MN.…”
Section: Complement In Kidney Diseasesmentioning
confidence: 99%
“…Membranous nephropathy (MN) is another form of immune-mediated glomerular injury in which immune complexes of immunoglobulins and complement accumulate in a granular pattern along the outer side of the GBM, leading to glomerular visceral epithelial cell detachment 90 (see the articles by Beck et al and Takano and Cybulsky). Seminal studies have identified several autologous antigens that are targets of antibody response in MN.…”
Section: Complement In Kidney Diseasesmentioning
confidence: 99%
“…PLA2R is a transmembrane protein located on the surface of human podocytes and colocalizes with IgG4 in the immune deposits of glomeruli in patients with IMN. Binding of the circulating anti-PLA2R antibody to the PLA2R antigen on glomerular podocytes to form an in situ immune complex activates a complement to cause podocyte and immune damage that results in urinary protein production, ultimately causing kidney damage (Glassock, 2012). Additionally, Beck et al found that serum anti-PLA2R antibodies were detectable in 70% of patients with IMN and detected at a low rate in people without kidney disease and other kidney patients (Hofstra & Wetzels, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…IMN is an autoimmune disease caused by endogenous antigens combined with specific antibodies in the circulation to form in situ immune complexes that are deposited in renal tissues. The anti-PLA2R antibody in circulation binds to PLA2R on the surface of podocytes to form an electrondense deposit under the foot process and epithelium, thereby activating the complement-forming membrane attack complex, causing podocyte and kidney damage (Glassock 2012). Several studies have demonstrated that the anti-PLA2R antibody is a key factor in the pathogenesis of IMN.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of the circulating anti-PLA2R antibody to the PLA2R antigen on glomerular podocytes to form an in situ immune complex activates a complement to cause podocyte and immune damage that results in urinary protein production, ultimately causing kidney damage (Glassock 2012). Additionally, Beck et al found that serum anti-PLA2R antibodies were detectable in 70% of patients with IMN and detected at a low rate in people without kidney disease and other kidney patients (Hofstra & Wetzels 2014).…”
Section: Introductionmentioning
confidence: 99%